2019
DOI: 10.1177/2045894019844480
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers in chronic thromboembolic pulmonary hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is a serious condition characterized with chronic organized thrombi that obstruct the pulmonary vessels, leading to pulmonary hypertension (PH) and ultimately right heart failure. Although CTEPH is the only form of PH that can be cured with surgical intervention, not all patients with CTEPH will be deemed operable. Some CTEPH patients still have a poor prognosis. Therefore, the determination of diagnostic and prognostic biomarkers of CTEPH is of great impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…Besides obstructive macrovascular disorder, CTEPH also encapsulates a "secondary arteriopathy" component of small sized pulmonary arterioles in which inflammation, oxidative stress and endothelial dysfunction play an important role [29]. In the current study, patients with CTEPH presented not only with mild capillaroscopic alterations similar to NVC changes observed in IPAH, but also with a higher degree of abnormal capillaries and capillary thrombi compared to IPAH patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Besides obstructive macrovascular disorder, CTEPH also encapsulates a "secondary arteriopathy" component of small sized pulmonary arterioles in which inflammation, oxidative stress and endothelial dysfunction play an important role [29]. In the current study, patients with CTEPH presented not only with mild capillaroscopic alterations similar to NVC changes observed in IPAH, but also with a higher degree of abnormal capillaries and capillary thrombi compared to IPAH patients.…”
Section: Discussionsupporting
confidence: 50%
“…For example, the imbalance between vasodilation and vasoconstrictor mediators, culminating in excessive vasoconstriction, endothelial and smooth muscle proliferation may account for pulmonary vascular remodeling as well as peripheral vascular changes in ΙPΑH [4]. Vascular endothelial growth factor (VEGF) and proinflammatory cytokines are likely mediators of chronic hypoxia-driven pulmonary and peripheral vascular remodeling in PAH, by mobilizing endothelial progenitor cells (EPCs) [26][27][28][29]. A severe reduction in circulating EPCs despite VEGF stimulus in late stages of SSc and its positive correlation with the reduction in capillary density may explain peripheral microvascular alterations [28], observed among entities of precapillary PH in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides an obstructive macrovascular disorder, CTEPH also encapsulates a "secondary arteriopathy" component of small sized pulmonary arterioles in which in ammation, oxidative stress and endothelial dysfunction play an important role [27]. In the current study, patients with CTEPH presented not only with mild capillaroscopic alterations similar to NVC changes observed in IPAH, but also with a higher degree of abnormal capillaries and capillary thrombi compared to IPAH patients.…”
Section: Discussionmentioning
confidence: 48%
“…For example, the imbalance between vasodilation and vasoconstrictor mediators, culminating in excessive vasoconstriction, endothelial and smooth muscle proliferation may account for pulmonary vascular remodeling as well as peripheral vascular changes in PH [4]. Vascular endothelial growth factor (VEGF) and proin ammatory cytokines are likely mediators of chronic hypoxia-driven pulmonary and peripheral vascular remodeling in pre-capillary PH, by mobilizing endothelial progenitor cells (EPCs) [24][25][26][27]. A severe reduction in circulating EPCs despite VEGF stimulus in late stages of SSc and its positive correlation with the reduction in capillary density may explain peripheral microvascular alterations [26], observed among various entities of precapillary PH in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In our view the last hypothesis (lysis and microembolism) is the most realistic as no major episode of clinically evident embolism occurred in the group of patients whose mass had disappeared at the follow-up. In our study, we did not monitor microembolism, but as reported in the literature there are several biomarkers that can be used in monitoring thrombo-microembolism [ 25 ]. Such monitoring is certainly warranted in our ghost patients and must be done in the future.…”
Section: Discussionmentioning
confidence: 99%